Challenges of motherhood in the voice of primiparous mothers: Initial difficulties - Carvalho, Júlia Maria das Neves (2017)
Objective: To identify the main difficulties first-time mothers experience in the postpartum period, during the first six months of the baby’s life. Methods: Level I qualitative, exploratory-descriptive study. The sample consisted of 11 first-time mothers of full-term healthy newborns. The data were collected through the “focus group” method. The mothers’ discourse was subject to content analysis, categorizing the registry units. Results: Three categories emerged from the data analyzed that indicate the mothers’ main difficulties in this period: postpartum recovery; baby care; marital relationship. Conclusion: The results indicate that, although motherhood is an event marked by positive emotions, the difficulties that emerge in the mothers’ daily life can interfere negatively in the quality of parenthood. In this scenario, the nurses play a determinant role in the enhancement of interventions that are sensitive to these needs and that, at the same time, favor these mothers and their families’ empowerment, thus optimizing the children’s development trajectories.